Sought solitude: On the “lecture-écriture” of Marguerite Duras and Pascal Quignard - Rita Rieger (Compendium, 2025)
In “Écrire” (1993), Marguerite Duras discusses the role of emotions such as loneliness, fear and despair in the act of reading and writing. Pascal Quignard’s essays “Lectio” and “La peur de devenir aveugle”, published in Petits Traités V (1990), also point to reading and writing and their relationship with emotions. In their fragmentary works both authors reflect on the nature of the subject of the writing or reading scene, which is ambivalently conceived as driving force and as dissolving in the act of writing or reading. This last aspect calls into question the subject’s experience of emotion and its narration. The aim of our contribution is to analyze the poetic and cultural functions of the relationship between writing, reading and emotions from the perspective of the narrativity of the cultural practices represented and considered in the texts.